PENERAPAN EVALUASI DIRI MADRASAH DALAM MENGOPTIMALKAN MUTU PENDIDIKAN DI MADRASAH ALIYAH PONDOK PESANTREN AN NAHDHLAH MAKASSAR - Magfira. S; Muh Anwar HM; Ridwan Idris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore and describe in depth the process of implementing Madrasah Self-Evaluation (EDM) in optimizing the quality of education at the An-Nahdlah Islamic Boarding School in Makassar. In addition, this study also identifies the supporting and inhibiting factors faced, and analyzes the real implications of EDM implementation on optimizing the quality of education at the institution. This research method uses a qualitative research type with a descriptive analysis approach. Data were collected through interviews, observations, and document studies to obtain a factual picture in the field. Data analysis was carried out by describing the managerial process based on the quality improvement cycle (PDCA) which includes the stages of planning, implementation, evaluation/analysis, and follow-up. The results show that the implementation of EDM at the An-Nahdlah Islamic Boarding School has been implemented through systematic stages, starting from the formation of a quality assurance team to the preparation of a data-based work plan. The main findings show significant improvements in Facilities and Infrastructure Standards, where the procurement of facilities such as projectors and internet access is now carried out in a data-driven manner based on evaluation results. Despite facing obstacles such as budget constraints and uneven technical understanding among some teachers, madrasas have successfully implemented gradual quality improvements with appropriate priorities. The research implications are that the implementation of EDM has had transformative implications for the quality culture in madrasas, namely a paradigm shift from mere administrative compliance to a collective commitment to continuous quality optimization (continuous improvement). Transparent evaluation results encourage madrasas to be more proactive and independent in identifying weaknesses and making improvements without waiting for external intervention, thus creating better managerial accountability.